Informed Trading and Momentum in the Corporate Bond Market - Li, Lifang; Galvani, Valentina (Review of Finance, 2021)
Abstract Taking advantage of the different trading behaviors of investors on same-issuer bonds, we show that informed trading lies at the core of the momentum effect for corporate bonds. We split the firm-level bond cross-section into top (nontop) bonds that are characterized by higher (lower) volumes of institution-sized trades. We show that top bonds attract more informed trading and transmit information faster than nontop bonds. We design specific top and nontop bond momentum strategies to capitalize on this informational heterogeneity. The results indicate that fast news spreading yields short-lived momentum in top bonds, whereas momentum in nontop bonds is strong and drawn-out due to slow information diffusion. These differences are concentrated in bond-level information-intensive periods and are not explained by differences in liquidity levels, systematic risk (including liquidity risk), bond characteristics, and market states. In particular, bond-level liquidity affects the momentum effect only by altering the rate at which news spreads.